PENGARUH BUDAYA ORGANISASI PADA KESUKSESAN IMPLEMENTASI SISTEM ERP: STUDI KASUS PT XYZ - Pamungkas, Firman Jati; Er, Mahendrawathi (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2018)
There is different outcome in the implementation of ERP systems in developing and developed countries, which lead to assumption of an organization cultural gap in corporate culture during the implementation process. It raises cultural issues when implemented in developing countries like Indonesia. This study attempts to analyze existing organizational culture conditions, according to Hofstedes cultural dimension theory, affect change management and ERP success. The study was conducted using qualitative methods including questionaire surveys, document reviews and interviews. First, survey with CVSCALE were administered to 30 ERP users in the case companies. Then, interviews are conducted with representative from the case companies with respect to change management and ERP implementation. Results from the interviews are analysed using pattern matching to obtain relationships between research constructs. The findings show that organizational culture influence the change management process and directly affect the success of implementation.